Chaperone networks in protein disaggregation and prion propagation - Winkler, Juliane; Tyedmers, Jens; Bukau, Bernd; Mogk, Axel (Journal of structural biology, 2012)
The oligomeric AAA+ chaperones Escherichia coli ClpB and Saccharomyces cerevisiae Hsp104 cooperate with cognate Hsp70/Hsp40 chaperone machineries in the reactivation of aggregated proteins in E. coli and S. cerevisiae. In addition, Hsp104 and Hsp70/Hsp40 are crucial for the maintenance of prion aggregates in yeast cells. While the bichaperone system efficiently solubilizes stress-generated amorphous aggregates, structurally highly ordered prion fibrils are only partially processed, resulting in the generation of fragmented prion seeds that can be transmitted to daughter cells for stable inheritance. Here, we describe and discuss the most recent mechanistic findings on yeast Hsp104 and Hsp70/Hsp40 cooperation in the remodeling of both types of aggregates, emphasizing similarities in the mechanism but also differences in the sensitivities towards chaperone activities.